Analisis Pengaruh Electronic Word of Mouth (EWOM) di Media Sosial Instagram Terhadap Minat Berkunjung Wisata ke Malang Raya (Studi Pada Akun Instagram Amazing Malang) - Wike Agustin Kurniasari; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This study scrutinized the partial and simultaneous effect of electronic Word of Mouth (EWOM) on Instagram towards visiting interests. EWOM is a form of marketing communication with positive or negative statements made by customers or former customers about products or companies to share their experiences on the internet. There are five EWOM variables used in this study, namely Concern for Other, Expressing Positive Feelings, Economic Incentives, Helping the Company and Platform Assistance. This study specifies the Instagram account â€œAmazing Malangâ€, which is an online media promotion strategy for tourists in Malang aiming to provide effective and efficient tourist information to increase visiting interest. The data collection used simple random sampling technique by distributing online questionnaires to Amazing Malang followers, namely 125 respondents who had been taken the awareness thereof. This research is classified as explanative statistical research using multiple linear regression analysis. Based on the results of simultaneous analysis, EWOM has a positive influence on the interest in visiting Malang by visiting Amazing Malang's social media. While based on the results of the partial analysis, the Expressing Positive Feelings and Helping the Company variables drove significant influence on visiting interest.